Serotonin Receptors Mediate Contractile Activity of Rat's Esophagus in-vivo - Lychkova Alla Eduard; Yuri Yu Golubev; Alexander M Puzikov (Archives of Organ Transplantation - Peertechz Publications, 2017)
Background: Serotonin (5-hydroxytryptamine, 5-HT) is a regulatory and biologically active neurotransmitter and a hormone in the CNS and many organs, including the esophagus. It is known that serotonin as well as acetylcholine stimulates contractile activity of the esophageal muscles. However, role of different serotonin receptors in the 5-HT contractile activity of the esophagus is insufficiently known. The aim: To determine which 5-HT receptors mediate serotonin contractile activity of the esophagus.  Subject and methods: This is an electromyography study of esophagus contractile activity of rat under serotonin stimulation of 5-HT3,4 and 5-HT2,1 receptors modulated separately. The role of different serotonin receptors in the 5-HT contractile activity of the esophagus was evaluated by measuring the amplitude and frequency of the slow wave electromyogram (EMG) by the noninvasive microelectrodes imposed on the adventitial layer of the esophagus. Results: Administration of the 5-HT3,4 receptors inhibitors excluded caused by serotonin the increment of EMG activity of the contractile activity of the esophagus. Administration of the 5-HT1,2 receptors inhibitors blocked the serotonin-induced increment of EMG activity of the contractile activity of the esophagus. Conclusion: Our results indicate that serotonin plays an important role in the regulation of the rat's esophagus contractility; the enhancing effect of 5-HT on contraction of the esophageal smooth muscles is mediated through the activation of 5-HT1,2 receptors expressed on the smooth muscle cells, and by activation of 5-HT3,4 receptors expressed on the ganglion neurons.